Entrepreneurial Orientation In The Last Decade: A Systematic Review - Mohammed Rabiu Musa; Kabiru Musa Yusuf; Idris Safiyanu Elatikpo (PT. Berkah Digital Teknologi, 2026)
Purpose of the study — This study aims to review the development of entrepreneurial orientation (EO) research from 2012 to 2021 by examining publication trends, geographical distribution, article types, data collection methods, and dominant research themes within a selected publisher / platform corpus. Research method—This study employed a targeted systematic review approach using the Systematic Quantitative Assessment Technique (SQAT) supported by PRISMA-based reporting procedures. Articles were identified through Google Scholar Advanced Search using the exact phrase “entrepreneurial orientation” in the article title and were limited to peer-reviewed English journal articles published between 2012 and 2021. The final corpus consisted of 100 articles from six selected publisher/platform sources: Sage, Springer, Elsevier, Emerald, Taylor & Francis, and Wiley. The articles were analyzed using descriptive classification and thematic synthesis. Result—The findings show that EO research was actively published during the review period, with the highest number of articles appearing in 2019. The United States, Spain, and China were the most represented countries, while Europe had the highest continental representation. Of the 100 reviewed articles, 93 were empirical and 7 were conceptual. Survey was the most frequently used data collection method, followed by interview, secondary data, and observation. The thematic analysis identified three dominant themes: EO magnitude, consequences of EO, and EO mechanisms, with EO magnitude being the most explored theme. Conclusion— This review indicates that EO research is empirically rich but remains uneven in terms of geographical coverage, conceptual development, and methodological diversity. Future studies should expand EO research into underrepresented contexts, strengthen conceptual contributions, apply more qualitative and mixed-method approaches, and examine EO consequences and mechanisms more deeply.